Building Professional Career of University Teacher in Russia - A. S. Sokolova; M. G. Sergeyeva; I. S. Samokhin (Научный диалог)
The problem of building a professional career of a University teacher in modern Russia is considered. The relevance of the study is determined by the fact that this problem is actively developed by supporters of the personal activity theory, which is currently the basis for planning the educational process in the substantive and methodological aspects. The basic concept of “education for career” is interpreted by the authors as a volume of knowledge, applied skills, cognitive activity scenarios, which is out-of-work in relation to the specialty and aimed at achieving high results in the profession (recognition by society, well-paid and socially significant positions) and obtaining positive emotions from their own work. In the study of support systems for career growth, the authors rely on the concept of the Russian professional education proposed by A. M. Novikov. Four main principles are taken into account: the humanization of education, its democratization and the emphasis on continuity and advance. The novelty of the research and its theoretical and practical significance lies in the allocation of three conditions for the career growth of a teacher of the University: the integration of pedagogical work into the system of life meanings and value hierarchy of the individual as their most important component; constant creative search, determined by the critical attitude to own professional level; readiness of a teacher to implement the activities of an innovative nature.